Millenial Consumer of Shopee Mall through Brand Trust and Fashion Lifestyle - Pratisti, Cahyani; De Yusa, Viola; Rahayu, Sri (International Journal of Psychosocial Rehabilitation, 2020)
Shopee Mall is one of the biggest e-commerce around the word eventhough fairy new. This research aimed toinvestigate the effect of brand trust and fashion lifestyle towards fashion buying decision on Shopee Mall either partially or simultaneously. This research used 300 millennial women which bought fashion items twice in a year. This quantitative causality research analyzed through multiple linear regression showed that brand trust and fashion lifestyle buying decision affect online fashion buying decision on Shopee Mall either partially and simultaneously. This research is very important because mistrust is happening issue in e-commerce.